System approach in urban transportation case: Huánuco region-Peru - Reyna-González, Julissa Elizabeth; Williams Chamoli Falcon, Andy; Eusebia Jesus Tolentino, Ines; Danly Leon Trujillo, Marx; León Trujillo, Betty (Edelweiss Applied Science and Technology, 2024)
The growing increase in vehicles produces serious congestion problems in urban centers; This situation raises questions about the control methods of the variables of interest in this problem. The case study presented is an approach to the topic and is based on a hypothetical scenario that is modeled and simulated with a systemic approach, considering the individual movement of the vehicles. A methodology is presented for the statistical analysis of the simulation results. The article shows the main aspects in the modeling of a basic traffic control system to simulate it and observe its behavior in the rhythm of arrivals, travel times and speeds, as well as monitoring traffic, in this sense the most important aspects will be illustrated. Relevant aspects that must be addressed in the configuration of a simulation experiment, such as determining the appropriate simulation time, the number of repetitions, the warm-up period, the evaluation of indicators to submit them to the normality test, and the application of techniques of variance reduction, experiencing congestion and evaluating measures to control excessive speed. The operation of traffic lights at intersections is also modeled and evaluated.